Traceability and Spectral Analysis of Transmission Error in Rotary Vector Planetary Gear Reducers - Xinping Zhu; Zhongxing Huang; Wuxi Shi; Liqing Shi (Applied Sciences)
The rotary vector planetary gear reducer is a critical joint reducer widely employed in various robotic systems. Due to numerous components and complex motion, the machining and assembly of its components significantly impact its motion accuracy. This paper utilizes transmission error (TE) traceability analysis and Fourier analysis to identify and characterize the TE components in rotary vector planetary reducers. By analyzing the motion characteristics of individual components, this study identifies the frequency characteristics of each component. Fourier frequency domain discretization, based on experimental TE measurements, verifies these characteristics, identifying the main factors affecting TE and providing theoretical support for enhancing transmission accuracy.